2012
DOI: 10.1007/s10096-011-1543-0
|View full text |Cite
|
Sign up to set email alerts
|

Serum pepsinogen and Helicobacter pylori infection—a Japanese population study

Abstract: The decreased ratio of serum pepsinogen (PG) I and II has good correlation with the presence of atrophic gastritis. A total of 1,540 residents aged 30-89 years were enrolled into this study to investigate which serum PG level of residents with Helicobacter pylori infection would represent an adjunct to the diagnosis and progression of atrophic gastritis. All participants received esophagogastroduodenoscopy. Serum antibody to H. pylori (anti-H. pylori) was measured by an enzyme-linked immunosorbent assay (ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 34 publications
1
6
1
Order By: Relevance
“…In a recent review, we found the prevalence of atrophy to be high (25% or more) in 5 of 9 studies from Africa, 4 and our serological data are consistent with a high prevalence of atrophy compared to 12% in Finland 21 or 27.6% in Japan. 22 We found no evidence that atrophy is more prevalent in the patients with intestinal type of gastric cancer, which is different from recent work in Germany. 19 Our data suggest that intestinal metaplasia can occur independently of gastric atrophy, whether assessed histologically or serologically.…”
Section: Discussioncontrasting
confidence: 99%
“…In a recent review, we found the prevalence of atrophy to be high (25% or more) in 5 of 9 studies from Africa, 4 and our serological data are consistent with a high prevalence of atrophy compared to 12% in Finland 21 or 27.6% in Japan. 22 We found no evidence that atrophy is more prevalent in the patients with intestinal type of gastric cancer, which is different from recent work in Germany. 19 Our data suggest that intestinal metaplasia can occur independently of gastric atrophy, whether assessed histologically or serologically.…”
Section: Discussioncontrasting
confidence: 99%
“… 15 2007–2009 Junior high school students General population Children No 1232 [16–17] Urine RAPIRAN Otsuka Pharmaceutical Co, Tokyo, Japan Domestic 1224 64 5.2 33 Toyoda et al . 47 2004–2007 Residents General population Adults No 1728 57.8 [30–89] Serum JHM-CAP, Kyowa, Medex Co., Ltd., Tokyo, Japan Domestic 1540 923 59.9 34 Tamura et al . 46 2008–2010 Participants of a cohort study General population Adults No 5167 [35–69] Urine Rapiran (Otsuka Pharmaceutical Co., Ltd., Tokyo, Japan) Domestic 5167 1881 36.4 35 Shimoyama et al .…”
Section: Resultsmentioning
confidence: 99%
“…The decrease of the serum pepsinogen I/II ratio is a marker of atrophic gastritis,43 and H. pylori -induced gastritis progresses to gastric atrophy 44. There was a significant correlation between gastric emptying and pepsinogen I/II ratio in the H. pylori -positive patients with FD 45.…”
Section: Discussionmentioning
confidence: 95%